Analyzing the Impact of IOS, Ownership, Sustainability Reporting, Firm Size, and Leverage on Firm Value: Evidence from Indonesian Manufacturing Firms - Pradnyawati, Sagung Oka; Kepramareni, Putu (Philippine Social Science Journal, 2025)
This study empirically analyzes how investment opportunities, ownership, sustainability reporting, firm size, and leverage influence firm value in the manufacturing sector. Based on multiple linear regression of data from 64 firms (2021–2023), results demonstrate that investment opportunities and sustainability reporting significantly enhance firm value, whereas managerial ownership, firm size, and leverage yield no significant impact. These findings imply that investors prioritize growth potential and ESG transparency over traditional financial metrics, suggesting companies should focus on strategic investments and sustainability initiatives to improve valuation. Future research is encouraged to incorporate mediating variables, such as profitability, and extend the analysis to diverse sectors and international contexts to broaden these insights.